Descrição matemática do fenômeno oscilatório durante a síntese eletroquímica dos filmes dos oxi-hidroxi compostos de cobalto (III) e durante a síntese dos compósitos deles com os polímeros condutores - Tkach, Volodymyr; Nechyporuk, Vasyl Vasylyovych; Slipenyuk, Oksana (Eclética Química, 2014)
The electrochemical behavior of the potentiostatic electrotransformation system from cobalt (II) salts to cobalt (III) oxyhydroxycompounds in the presence of fluoro ions (which promotes the dissolution of cobalt(III) oxyhydroxycompounds) on platinum, which acts as an oscillator, has been described mathematically. The corresponding mathematical model was analyzed using linear stability theory and bifurcation analysis. It is shown that the oscillations in this system occur because of the interaction between the film particles. For the case of electrosynthesis of polymeric composites of cobalt oxyhydroxy compounds with conductive polymers in the absence of fluoro ions, the factor most responsible for the oscillatory behavior is the polymerization factor.